Thermodynamic and Magnetic Properties of Diatomic Molecules for Non-central Potentials under the Influence of External Magnetic Fields - Cari, Cari; Suparmi, A; Permatahati, Luthfiya Kurnia (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2023)
This paper studies the thermodynamic and magnetic properties of some diatomic molecules governed by Scarf and Morse non-central potentials under external magnetic and electric fields. The Schrodinger equation with Scarf and Morse non-central potentials is solved using Supersymmetric WKB quantization conditions to obtain the energy equation and wave function. The influence of the magnetic and electric fields on the energy eigenvalue was discussed. The results show that energy increases with the increasing magnetic field and decreases with the increasing electric field. Moreover, the thermodynamic and magnetic properties involving internal energy, free energy, specific heat capacity, entropy, magnetization, magnetic susceptibility, and persistent current were determined by calculating the partition function. The internal energy increases linearly with the increasing magnetic field for a given temperature. Meanwhile, the specific heat capacity decreases with the increasing magnetic field. We point out that the presence of magnetic and electric fields makes the system exhibit diamagnetic behavior.